2005
DOI: 10.1185/030079905x65510
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of select biologic and DMARD monotherapy and combination therapy in the treatment of rheumatoid arthritis: results from the RADIUS observational registry

Abstract: These data from routine rheumatology clinical practice settings highlight the effectiveness of common biologic and DMARD therapies, and provide additional data beyond those of randomized, controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Failure to suppress the CRP is a predictor of a poor response to TNF inhibitors. 18 However, the ESR and CRP are not sufficient to determine treatment responses. Despite improvement of acute phase reactants, some patients will have progression of joint damage.…”
Section: Biomarkers For Ra Disease Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Failure to suppress the CRP is a predictor of a poor response to TNF inhibitors. 18 However, the ESR and CRP are not sufficient to determine treatment responses. Despite improvement of acute phase reactants, some patients will have progression of joint damage.…”
Section: Biomarkers For Ra Disease Activitymentioning
confidence: 99%
“…Many instruments have been validated that can be incorporated into routine clinical practice to aid in treatment decisions with the goal of optimizing clinical responses and reducing joint damage from RA. 18 In randomized clinical trials, all of these agents have been shown to be effective in reducing clinical signs of inflammation in RA patients who have failed synthetic DMARDs. Multiple studies have demonstrated significant benefits of early treatment with TNF-alpha inhibitors combined with methotrexate.…”
Section: ■■ Conclusionmentioning
confidence: 99%
See 3 more Smart Citations